Morphological characterization of red rice germplasm of Himachal Pradesh and identification of potential genotype for yield and biotic stress tolerance - Alagappan, Praveenkumar; Bhardwaj, Neelam (Journal of Cereal Research, 2025)
The present investigation was carried out in Rice &Wheat Research Centre Malan of with thirty-five red rice germplasm lines collected across Himachal Pradesh Observations were recorded on twelve quantitative six grain quality traits. Analysis of variance showed presence of variability for all traits except flag leaf length, harvest index and grain breadth among the germplasm lines. Analysis of parameter of variability exhibited high heritability coupled with high genetic advance as percent of mean for biological yield per plant, thousand grain weight and L:B ratio which indicated the presence of high additive gene action and selection for such traits may be beneficial in future breeding programme. The mean performance of genotypes was compared with best check with particular trait and genotypes- Deval, HPR-2913, HPR-2908 were found to be promising for most of the traits including grain quality. The disease reaction for leaf and neck blast among genotypes indicated that, IC-12180, HPR-2800, HPR-2795, HPR-2913 and HPR-2914 were found to be resistance to both blast disease.